2002
DOI: 10.1051/0004-6361:20021481
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous optical and X-ray observations of flares and rotational modulation on the RS CVn binary HR 1099 (V711 Tau) from the MUSICOS 1998 campaign

Abstract: Abstract. We Maps of the distribution of the spotted regions on the photosphere of the binary components were derived using the Maximum Entropy and Tikhonov photometric regularization criteria. Rotational modulation was observed in Hα and He  D 3 in anti-correlation with the photometric light curves. Both flares occurred at the same binary phase (0.85), suggesting that these events took place in the same active region. Simultaneous X-ray observations, performed by ASM on board RXTE, show several flare-like … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 38 publications
(66 reference statements)
5
31
0
Order By: Relevance
“…This mechanism presented by Matese & Whirtmere (1983) and developed by Applegate (1992) and Lanza et al (1998), has been used in the study of several RS CVn systems such as SZ Psc (Kalimeris et al 1995), RT Lac, RS CVn, WW Dra, etc. (Lanza & Rodonó 1999), XY UMa (Sowell et al 2001) and HR 1099 (García-Álvarez et al 2003;Frasca & Lanza 2005;Lanza 2006). Applegate (1992), described the initial model in which the orbital period variation is due to the gravitational coupling of the orbit to changes in the quadrupole moment (rotational oblateness) of a magnetically active star in the system.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism presented by Matese & Whirtmere (1983) and developed by Applegate (1992) and Lanza et al (1998), has been used in the study of several RS CVn systems such as SZ Psc (Kalimeris et al 1995), RT Lac, RS CVn, WW Dra, etc. (Lanza & Rodonó 1999), XY UMa (Sowell et al 2001) and HR 1099 (García-Álvarez et al 2003;Frasca & Lanza 2005;Lanza 2006). Applegate (1992), described the initial model in which the orbital period variation is due to the gravitational coupling of the orbit to changes in the quadrupole moment (rotational oblateness) of a magnetically active star in the system.…”
Section: Discussionmentioning
confidence: 99%
“…However, in some cases, no clear rotational modulation of chromospheric diagnostics has been detected despite the contemporaneous wave-like behaviour in the photometry (see, e.g., Catalano et al 2000). In such cases, the distribution of the active regions, as revealed by the Hα emission, may be more homogeneously distributed in the base of the chromosphere than in the photosphere or in other atmospheric layers, as proposed, e.g., by García-Alvarez (2003). In addition, the Hα line may originate in other physical processes, like flares and prominences.…”
Section: Hα Linementioning
confidence: 96%
“…Figure 2 shows the light curves for both observations; note that both light curves are relatively flat and devoid of large flare activity. Several authors have reported coronal rotational modulation on active stars (e.g., Drake et al 1994;Audard et al 2001;García-Alvarez et al 2003), including AB Dor (Kuerster et al 1997). However, as shown in Figure 2 (bottom), no obvious modulation of the coronal emission with orbital phase was seen on either star, although in the case of AB Dor, the observation only covers slightly more than one rotational period.…”
Section: Photometrymentioning
confidence: 99%